Investigation on pressure variation of steam on efficiency of steam powered motor / Siti Norshafiqah Kamal Azman Shah - Kamal Azman Shah, Siti Norshafiqah (2022)
A steam engine is a heat engine that performs mechanical work using steam as its working fluid. The steam engine uses the force produced by steam pressure to push a piston back and forth inside a cylinder. This pushing force can be transformed, by a connecting rod and crank, into rotational force for work. However, for high efficiency, the steam must fall through a wide temperature range because of its expansion within the engine. In this study, different pressure of steam relative to different load weight and different engine motor speed on a steam powered motor. The result for efficiency from the research and experiment will be taken. The pressure 1 bar to 3 bar and the weight from 0 gram to 50 gram with interval of 10 gram. The steam may be heated beyond the temperature at which it is produced by boiling water. The efficiency of steam motor may increase along with higher temperature and lower load weight.